2015
DOI: 10.1007/s11357-015-9791-z
|View full text |Cite
|
Sign up to set email alerts
|

Frailty prevalence and related factors in the older adult—FrailTURK Project

Abstract: Frailty is one of the geriatric syndromes and has an important relationship with mortality and morbidity. The aim of this study is to present the characteristics, prevalence, and related factors of frailty in older adults in our country. The study included 1126 individuals over 65 years of age from 13 centers. Frailty was evaluated using the Fried Frailty criteria, and patients were grouped as Bfrail,^Bpre-frail,^and Bnon-frail.N utritional status was assessed with BMini Nutritional Test,^psychological status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
64
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 27 publications
17
64
2
7
Order By: Relevance
“…This result differs from those of other studies that observed this relationship among older adults who lived with family members 25 and those living alone 2 , 4 , 7 . Social bonds and the support experienced can influence the health maintenance, promoting adaptive behavior in stress situations.…”
Section: Discussioncontrasting
confidence: 93%
“…This result differs from those of other studies that observed this relationship among older adults who lived with family members 25 and those living alone 2 , 4 , 7 . Social bonds and the support experienced can influence the health maintenance, promoting adaptive behavior in stress situations.…”
Section: Discussioncontrasting
confidence: 93%
“…In addition, older individuals with higher levels of psychological well‐being tended to be associated with less frailty in the future . Similarly, an association between frailty and depression has been observed in outpatient clinics . In the present study, we observed that the presence of depressed mood was associated with prefrailty status.…”
Section: Discussionsupporting
confidence: 78%
“…18 Similarly, an association between frailty and depression has been observed in outpatient clinics. 19 In the present study, we observed that the presence of depressed mood was associated with prefrailty status. Additionally, more than 20% of the participants with prefrailty had low physical activity, which was the main domain defined in prefrailty.…”
Section: Discussionsupporting
confidence: 50%
“…Cohen’s d ES for mean scores was 0.75El Zoghbi et al, 2014 [36]Cross-sectionalAsia (Lebanon); n  = 111; ≥65 years; 50.4% womenInstitutionalized older adultsSOF index [51, 52]MNA® [41]37.9% frailty and 36.9% pre-frailty;12.6% malnourishment and 48.7% at risk of malnutritionThe MNA score was inversely associated with the SOF Frailty Index (standardized beta coefficient − 0.18, 95% CI -1.46- -0.13). Mean scores comparison: small Cohen’s d ES (0.24) in malnutrition vs. risk of malnutrition, medium ES (0.65) in malnutrition vs. normal, and large ES (0.89) in risk of malnutrition vs. normalEyigor et al, 2015 [26]Cross-sectionalEurope (Turkey); n  = 1126; age range (65–85 years); 65.7% womenCommunity-dwelling older adults (living on their own or in a family house) and those living in nursing homesFried frailty phenotype [3]MNA® [41]39.2% frailty and 43.3% pre-frailty; 5% malnutrition and 27.5% at risk of malnutritionMalnutrition increased the risk of frailty (OR 48.545, 95% CI 6.647–354.554). Large Hasselblad & Hedges’ d ES (0.89).Jürschik et al, 2014 [30]LongitudinalEurope (Spain); n  = 640; age, mean ± SD: 81.3 ± 5.0 years; 60.3% womenCommunity-dwelling older adults from the FRALLE surveySlightly modified Fried frailty phenotype [3]: changes in metrics to characterize frailty [55]MNA®, MNA-SF® [41]9.6% frailty and 47% pre-frailty; 1.9% malnutrition and 19.8% at risk of malnutritionBoth the MNA (0.75, p  < 0.001) and the MNA-SF (0.80, p  < 0.001) were accurate in identifying frailty.…”
Section: Resultsmentioning
confidence: 99%